Efficacy of portable sleep monitoring device in diagnosing central sleep apnea in patients with congestive heart failure - Tung, Pi-Hung; Hsieh, Meng-Jer; Chuang, Li-Pang; Lin, Shih-Wei; Hung, Kuo-Chun; Lu, Cheng-Hui; Lee, Wen-Chen; Hu, Han-Chung; Wen, Ming-Shien; Chen, Ning-Hung (Frontiers in Neurology, 2022)
Introduction: Central sleep apnea (CSA) is a common and serious comorbidity in patients with heart failure (HF) which tends to be underdiagnosed and has not been widely studied. Overnight polysomnography (PSG) is the gold standard for diagnosing CSA; however, the time and expense of the procedure limit its applicability. Portable monitoring (PM) devices are convenient and easy to use; however, they have not been widely studied as to their effectiveness in detecting CSA in HF patients. In the current study, we examined the diagnostic value of PM as a screening tool to identify instances of CSA among HF patients. Methods: Twenty-two patients under stable heart failure conditions with an ejection fraction of < 50% were enrolled. All patients underwent PM as well as overnight PSG within a narrow time frame. The measurements of apnea-hypopnea index (AHI), hypopnea index (HI), central apnea index (CAI) and obstructive apnea index (OAI) from PSG, automatic scoring and manual scoring of PM were recorded. Comparison of the results between PSG and PM (automatic and manual scoring) were used to assess the accuracy of PM. Results: Among the participants, eleven presented CSA in PSG analysis. The AHI measurements using manual scoring of PM showed significant correlation with that of using PSG (r = 0.69; P = 0.01). Nonetheless, mean AHI measurements were observed statistically significant differences between PSG and automatic scoring of PM (40.0 vs 23.7 events/hour, respectively; P <0.001) as well as between automatic and manual scoring of PM (23.7 vs 29.5 events/hour; P value <0.001). Central sleep apnea was detected by the PM; however, the results were easily misreading as obstructive apnea, particularly in automatic scoring. Conclusions: PM device could be used to identify instances of central sleep apnea among HF patients. The results from PM were well correlated with standard PSG results and manual scoring was preferable to automated scoring.